Comparable effect of aliskiren or a diuretic added on an angiotensin II receptor blocker on augmentation index in hypertension: a multicentre, prospective, randomised study. Issue 1 (11th March 2017) - Miyoshi, Toru; Murakami, Takashi; Sakuragi, Satoru; Doi, Masayuki; Nanba, Seiji; Mima, Atsushi; Tominaga, Youkou; Oka, Takafumi; Kajikawa, Yutaka; Nakamura, Kazufumi; Ito, Hiroshi
Abstract : Background: The effects of antihypertensive drug combination therapy on central blood pressure (BP) and augmentation index (AI) have not been fully elucidated. We investigated the effects of the direct renin inhibitor, aliskiren, or a diuretic added to an angiotensin II receptor blocker on AI in patients with essential hypertension. Methods: A 24-week, prospective, multicentre, randomised, open-label study enrolled 103 patients already treated with valsartan. Participants were randomly allocated to receive either valsartan with aliskiren (V+A), or valsartan with trichlormethiazide (V+T). The primary outcome was the change in AI derived from radial artery tonometry. Secondary outcome measures included systolic and diastolic BP, cardio-ankle vascular index (CAVI, which reflects arterial stiffness) and urinary 8-hydroxydeoxyguanosine concentration. Results: After 24 weeks, systolic and diastolic BP were significantly reduced in both groups to a broadly comparable extent. There was no significant difference in AI at the end of the study between the V+A group and the V+T group (between-group difference: −2.3%, 95% CI −6.9% to 2.2%, p=0.31). Central BP at the end of the study also did not differ between the two groups (p=0.62). There was no significant difference in the CAVI between the groups at the end of the study. Urinary 8-hydroxydeoxyguanosine concentration was significantly lower in the V+A group than in the V+T group (p<0.01), suggesting that V+A attenuated oxidative stress more than V+T. Conclusion: The combination of valsartan and aliskiren had an effect on AI comparable with that of the combination of valsartan and trichlormethiazide. UMIN Clinical Trial Registration number: UMIN000005726.